(untitled) (Research, Society and Development, 2021)
The aim of this study is to discuss the impacts of Covid-19 infection in children based on scientific evidence. This is an integrative literature review, guided by the PICO and PRISMA guidelines, in which searches were performed in the LILACS, MEDLINE, IBECS, LIS and BDENF databases during April and May 2020. The assessment of the level of evidence was obtained through the Oxford Center for Evidence-based Medicine classification. Regarding the inclusion criteria, the time frame was not defined due to the contemporaneity of the phenomenon studied, and articles that fully contemplated the objective of the study were inserted. Thus, eight articles were included in this study. They highlighted that newborns, infants and children are less affected or have fewer positive clinical diagnoses for the new coronavirus than adults, since most of them have mild or difficult-to-recognise symptoms and in some cases are asymptomatic, but social distancing and everyday preventive behaviors continue to be important for all age groups. In the scenario of the Covid-19 pandemic, contamination of children is rare, although they are susceptible to the virus, most of them present mild and short-lived symptoms and those who are asymptomatic should be considered.